First off Label Endovascular Clinical Experience to Treat Diffuse Cerebral Venous Sinus Thrombosis Using the INARI FlowTriever System: Case Report - Bushnaq, Saif; Kareem, Samer Abdul; Liaw, Nicholas; Alenzi, Bader; Ahmed, Muhammad Khaleeq; Bushnaq, Merna; Zaidat, Osama O. (Frontiers in Neurology, 2021)
Cerebral Venous Sinus Thrombosis (CVST) is a rare stroke with a wide range of symptomatology at presentation ranging from headache, focal weakness, and coma. Anticoagulation remains the mainstay of treatment. However, in a subset of patients; endovascular treatment can be potentially beneficial. Here we describe the first reported clinical experience using the INARI FlowTriever system to treat a patient presented with focal weakness and found to have diffuse CVST.